Did Partial Globalization Increase Inequality? Did Inequality Stimulate Globalization Backlash? The case of the Latin American Periphery, 1950-80 - Jörg Baten (Center for Economic Studies and ifo Institute (CESifo), 2002)
Inequality is an important threat to the globalization of the world economy that we experience today. This contribution uses a new measure of inequality: heigth inequality. It covers not only wage recipients, but also the self-employed, the unemployed, housewifes, children, and other groups who may not be participating in a market economy, for the 1950-80 period. It turns out that within-country inequality is higher in time periods of greater openness.We also find that inequality leads to a globalization backlash . The closing of commodity and capital markets did always take place during - or 5-10 years after - inequality peaks.
Keywords: 330; inequality; globalization; anthropometrics; globalisation